Safety and efficacy of flecainide for patients with catecholaminergic polymorphic ventricular tachycardia: A systematic review and meta-analysis. Issue 34 (August 2019) - Wang, Guangqiang; Zhao, Na; Zhong, Shu; Wang, Yingrong; Li, Jianping
Abstract: Background: Owing to reports of recurrent cardiac events in some catecholaminergic polymorphic ventricular tachycardia (CPVT) patients using β-blockers, safer alternatives are being investigated. Flecainide is an alternative adjunctive anti-arrhythmic agent known to provide incomplete protection to CPVT patients. Methods: To investigate the efficacy and tolerability of flecainide, we searched 4 databases for retrospective cohort studies (RCs) and randomized controlled trials (RCTs) investigating the efficacy and safety of flecainide for CPVT patients. Data were extracted and analyzed (risk ratio [RR] or mean difference [MD]) using RevMan software. Seven RCs and 1 RCT (333 CPVT patients; 152 patients treated with flecainide) were identified. Results: Flecainide monotherapy was superior to standard therapy in alleviating the risk of arrhythmic events (RR = 0.46, confidence interval [CI] = [0.38, 0.56], P  < .00001) and exercise-induced arrhythmia scores (MD = −0.39, CI = [−0.74, −0.05], P  = .03). Combination therapy of flecainide and β-blockers was superior to β-blocker monotherapy in reducing the risk of arrhythmic and symptomatic events (RR = 0.29, CI = [0.13, 0.69], P  = .005; RR = 0.36, CI = [0.20, 0.62], P  = .0003, respectively), peak heart rate (MD = −16.81, CI = [−28.21, −5.41], P  = .004), and exercise-induced arrhythmia scores (MD = −1.87, CI = [−2.71, 1.04], P  < .0001). Flecainide did not increase the risk of all side effects (RR = 0.76, CI = [0.42, 1.40], P  = .38) compared to that with β-blockers alone. No deaths were reported among patients treated with flecainide. Conclusions: Flecainide is an effective and safe anti-arrhythmic agent, and its use as a monotherapy might be a good alternative for CPVT patients with β-blocker intolerance. Combination therapy was superior to β-blocker monotherapy. More randomized clinical trials are required to explore the long-term efficacy and safety of flecainide in these patients. Abstract : Supplemental Digital Content is available in the text